2002
DOI: 10.1007/978-3-540-46138-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters—Electronic Service Delivery by Municipalities?

Abstract: Abstract. The development of e-government in the Netherlands shows two different worlds. The large national organisations implement Electronic Service Delivery (ESD) fairly successfully, while municipalities are slow to adopt ESD. This is a pity, since municipalities account for over 70% of the public services. They are expected to implement ESD on their own although they lack the necessary resources and distributed development is inefficient. In this paper we address the role of municipalities in the real and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In the United States, Kaylor, Deshazo and Van Eck (2002) analyzed the municipalities and the use of ICT for the development of public services on the internet, proposing means to measure the implementation of e-government among different American cities. Leenes and Svensson (2002) identified differences in the development of e-government between the national and municipal level in the Netherlands and found that while the national government was successful, municipalities were slow and inefficient with few resources to deploy e-government. Moon (2002) identified similar results in adopting e-government in US local governments, and suggested that there are barriers toward municipal e-government progress such as lack of financial, technical, personnel, and legal capacity.…”
Section: E-government Smart Cities and Ict Infrastructure In Brazilimentioning
confidence: 99%
“…In the United States, Kaylor, Deshazo and Van Eck (2002) analyzed the municipalities and the use of ICT for the development of public services on the internet, proposing means to measure the implementation of e-government among different American cities. Leenes and Svensson (2002) identified differences in the development of e-government between the national and municipal level in the Netherlands and found that while the national government was successful, municipalities were slow and inefficient with few resources to deploy e-government. Moon (2002) identified similar results in adopting e-government in US local governments, and suggested that there are barriers toward municipal e-government progress such as lack of financial, technical, personnel, and legal capacity.…”
Section: E-government Smart Cities and Ict Infrastructure In Brazilimentioning
confidence: 99%
“…Web sites (Leenes and Svensson, 2002). The implementation of e-government is a complex and ambitious project that requires considerable prioritisation, scheduling and planning.…”
Section: Kiosksmentioning
confidence: 99%
“…Each municipality delivers between 200 and 400 kinds of product and service to its citizens. Different countries have different structures, and services that are delivered by public sector organizations in some countries may be delivered by private sector organizations elsewhere [30]. The implementation of e-government is a complex and ambitious project that requires considerable prioritization, scheduling and planning.…”
Section: Definition Of the Role Of Kiosks In E-governmentmentioning
confidence: 99%
“…Among them was the city of Enschede 2 , which is also largely unaware of the possibilities LKBS technology offers. The development of electronic service delivery primarily takes place at the local level in the Netherlands (Leenes and Svensson, 2002). This makes the chances that smaller projects with less resources than the Enschede project make use of advanced tools, is remote.…”
Section: A Field Tripmentioning
confidence: 99%
“…We also have partial answers. To name but a few: the development of electronic services is an organisational problem more than a technical one (Bellamy and Taylor, 1998), there is hardly any political pressure to implement service delivery reforms (Hoogwout, 2001) and development is very fragmented in the sense that the wheel is reinvented in many places (Leenes and Svensson, 2002).…”
Section: Introductionmentioning
confidence: 99%